The Rising Cost of Child Care in the United States: A Reassessment of the Evidence - Chris M. Herbst (Institute for the Study of Labor (IZA), 2015)
Anecdotal evidence suggests that the cost of child care in the U.S. has increased substantially over the past few decades. This paper marshals data from a variety of sources to rigorously assess the issue. It begins by using nationally representative survey data to trace the evolution in families' child care expenditures. I find that the typical family currently spends 14 percent more on child care than it did in 1990. This is less than half the increase documented in previous work. Interestingly, low-income families spend the same amount or less on child care, while their high-income counterparts spend considerably more. Despite this divergence, families at all income levels allocate the same share of income to child care as they did several decades ago. The next section of the paper draws on establishment- and individual-level data to examine trends in the market price of child care. The evidence suggests that after persistent, albeit modest, growth throughout the 1990s, market prices have been essentially flat for at least a decade. In the paper's final section, I analyze several features of the child care market that may have implications for prices, including the demand for child care, the skill-level of the child care workforce, and state regulations. A few findings are noteworthy. First, I show that child care demand stagnated around the same time that market prices leveled-off. Second, although the skill-level of the child care workforce increased in absolute terms, highly-educated women increasingly find child care employment less attractive than other occupations. Finally, child care regulations have not systematically increased in stringency, and they appear to have small and inconsistent effects on market prices. Together, these results indicate that the production of child care has not become more costly, which may explain the recent stagnation in market prices.
Keywords: I28; J01; J08; J20; 330; child care costs; child care demand; child care regulations; parental employment